Integrating management tools and concepts to develop an estuarine planning support system: A case study of the Humber Estuary, Eastern England. Issue 1 (15th November 2015) - Lonsdale, Jemma-Anne; Weston, Keith; Barnard, Steve; Boyes, Suzanne J.; Elliott, Michael
Abstract: Estuaries are important because of their multiple uses and users which often makes them challenging to manage since management must strike a balance between the needs of users, the estuaries' ecological and economic value and the context of multiple legislative drivers. To facilitate management we have therefore developed an Estuarine Planning Support System (EPSS) framework using the Humber Estuary, Eastern England, as a case study which integrates the current legislation tools and concepts. This integrated EPSS framework is an improvement on previous approaches for assessing cumulative impacts as it takes into account legislative drivers, management tools and other mechanisms for controlling plans/projects specific to the estuary. It therefore enables managers and users to assess and address both the current state and the way in which a new industrial, port or urban development could impact an estuary in an accessible and understandable framework. Highlights: The case for an integrated Estuarine Planning Support System (EPSS) is presented. The EPSS is a Decision Support System to aid estuarine managers. The EPSS merges a set of current concepts across the natural and social sciences. Shows the need to reflect governance with ecological and socio–economic constraints Presented for the Humber Estuary, UK, the EPSS is generic for estuaries worldwide.